Successful Immunomodulatory Treatment of COVID-19 in a Patient With Severe ACTH-Dependent Cushing’s Syndrome: A Case Report and Review of Literature - Popovic, Bojana; Radovanovic Spurnic, Aleksandra; Velickovic, Jelena; Plavsic, Aleksandra; Jecmenica-Lukic, Milica; Glisic, Tijana; Ilic, Dusan; Jeremic, Danka; Vratonjic, Jelena; Samardzic, Vladimir; Gluvic, Zoran; Adzic-Vukicevic, Tatjana (Frontiers in Endocrinology, 2022)
Introduction: Patients with Cushing’s syndrome (CS) represent a highly sensitive group during corona virus disease 2019 (COVID-19) pandemic. The effect of multiple comorbidities and immune system suppression make the clinical picture complicated and treatment challenging. Case report: A 70-year-old female was admitted to a covid hospital with a severe form of COVID-19 pneumonia that required oxygen supplementation. Prior to her admission to the hospital she was diagnosed with adrenocorticotropic hormone (ACTH)-dependent CS, and the treatment of hypercortisolism had not been started yet. Since the patient’s condition was quickly deteriorating, and with presumed immune system suppression due to CS, we decided on treatment with intravenous immunoglobulins (IVIg) that enabled quick onset of immunomodulatory effect. All comorbidities were treated with standard of care. The patient’s condition quickly stabilized with no direct side effects of a given treatment. Conclusion: Treatment of COVID-19 in patients with CS faces many challenges due to the complexity of comorbidity effects, immunosuppression and potential interactions of available medications both for treatment of COVID-19 and CS. So far, there are no guidelines for treatment of COVID-19 in patients with active CS. It is our opinion that immunomodulating therapies like IVIg might be an effective and safe treatment modality in this particularly fragile group of patients